Single Mother dalam Membangun Ekonomi Keluarga - Angelus Ewid; Benedhikta Kikky Vuspitasari (EKONOMI & SOSIAL, 2020)
ABSTRACT The purpose of writing to know the causes of single mother, the impact and efforts of single mothers to overcome these impacts, using qualitative research methods with phenomenological approaches that highlight the life of single mothers. Results showed that the causes of single mothers were economic stress, domestic violence, death of a spouse and infidelity. The impact, although single mother condition is not expected but this condition also has a positive impact on cases that harm women (domestic violence and infidelity). The negative impact experienced besides psychic then financial condition becomes the impact that most affects single mother. The efforts of single mothers to overcome the negative impact sparked by reorganize their family life after becoming a single mother, motivating themselves to stay strong and spirited by thinking positively and optimistically, in addition to organizing the family economy in the field of trade and beauty services, where the main priority of single mother is educating, raising her children and meeting the economic needs of the family, in addition to the support of large single mother families is very influential.